PHYTOCHEMICAL ASSESSMENT ON VARIOUS EXTRACTS OF CALOTROPIS GIGANTEA (L.) R. BR. THROUGH GC-MS - SURESHKUMAR. P, (International Journal of Pharma and Bio Sciences, 2013)
The present study reports the phytochemical property of Calotropis gigantea, commonly known as wasteland weed or milkweed. Acetone, Methyl alcohol and Chloroform extracts of the plant were reviewed by using GC-MS. The numbers of compounds are greatly varies one solvent to another solvent. The maximum numbers of (70) compounds were recorded in the chloroform extract. The acetone and methyl alcohol possesses 23 and 21 compounds respectively. The compounds present in these extracts are useful for various human welfares.